1997
DOI: 10.1136/jnnp.63.6.784
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microembolism in patients with stroke or transient ischaemic attack as a risk factor for early recurrence

Abstract: The incidence of early recurrence in 32 patients who had had a transient ischaemic attack or stroke in the anterior circulation was studied. Patients with a potential cardiac source of embolism were excluded from the study. All patients had transcranial Doppler (TCD) monitoring of the symptomatic middle cerebral artery for microembolic signal detection within seven days from the onset of symptoms. Four patients had early recurrence during a mean follow up of 15 (SD11) days. All early recurrences occurred in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
0
15
1
1
Order By: Relevance
“…Consistent with our findings, the Stroke Data Bank investigators found that the 30-day cumulative rate of early recurrence was highest in the group of patients with large-vessel atherothrombotic stroke and lowest in the group with smallvessel lacunar infarction, with intermediate rates for cardioembolic and cryptogenic stroke subtypes. 9 The higher rate of early recurrence in patients with large-vessel atherosclerosis compared with other infarct subtypes may be the result of cerebral microembolism 38,39 from plaque ulceration and lumen thrombus. 40 While we did not distinguish between extracranial and intracranial atherosclerosis in our classification of large-vessel disease, such a distinction may be important, given that patients with intracranial atherosclerosis are also at increased risk of early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, the Stroke Data Bank investigators found that the 30-day cumulative rate of early recurrence was highest in the group of patients with large-vessel atherothrombotic stroke and lowest in the group with smallvessel lacunar infarction, with intermediate rates for cardioembolic and cryptogenic stroke subtypes. 9 The higher rate of early recurrence in patients with large-vessel atherosclerosis compared with other infarct subtypes may be the result of cerebral microembolism 38,39 from plaque ulceration and lumen thrombus. 40 While we did not distinguish between extracranial and intracranial atherosclerosis in our classification of large-vessel disease, such a distinction may be important, given that patients with intracranial atherosclerosis are also at increased risk of early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…As covered in the introduction, in patients with carotid stenosis, a large number of studies suggest that asymptomatic embolic signals have clinical significance. 6 -10 Prospective studies in patients with symptomatic carotid stenosis 8,10 and in patients with asymptomatic carotid stenosis 24 have found embolic signals to be an independent predictor of combined stroke and transient ischemic attack risk. Their high frequency compared with the clinical end points of stroke and transient ischemic attack, combined with their clinical significance, suggest that they may be useful surrogate markers for the evaluation of new antithromboembolic agents.…”
Section: Kaposzta Et Al Switching Off Embolization From Plaquementioning
confidence: 99%
“…Furthermore, the presence of embolic signals in the ipsilateral middle cerebral artery independently predicts future stroke and risk of transient ischemic attack in patients with symptomatic carotid stenosis. 8,10 The current treatment of choice for symptomatic carotid stenosis Ն70% is carotid endarterectomy. 1,2 In patients with 50% to 70% stenosis there is still an increased stroke risk, but the benefits of operation are unclear.…”
mentioning
confidence: 99%
“…12 A few studies have suggested that microembolism may be a risk factor for early ischemic recurrence (EIR). [13][14][15] However, none of their designs permitted them to control for the effect of potential confounding variables, such as severe carotid stenosis or thick AAA. The purpose of our study was to assess the independent contribution of microembolism to the risk of EIR in patients with cerebral ischemia of presumed arterial origin.…”
mentioning
confidence: 99%